Evolution of crystallins for a role in the vertebrate eye lens. (26th February 2013) - Slingsby, Christine; Wistow, Graeme J.; Clark, Alice R.
Abstract: The camera eye lens of vertebrates is a classic example of the re‐engineering of existing protein components to fashion a new device. The bulk of the lens is formed from proteins belonging to two superfamilies, theα ‐crystallins and theβ γ ‐crystallins. Tracing their ancestry may throw light on the origin of the optics of the lens. Theα ‐crystallins belong to the ubiquitous small heat shock proteins family that plays a protective role in cellular homeostasis. They form enormous polydisperse oligomers that challenge modern biophysical methods to uncover the molecular basis of their assembly structure and chaperone‐like protein binding function. It is argued that a molecular phenotype of a dynamic assembly suits a chaperone function as well as a structural role in the eye lens where the constraint of preventing protein condensation is paramount. The main cellular partners ofα ‐crystallins, theβ ‐ andγ ‐crystallins, have largely been lost from the animal kingdom but the superfamily is hugely expanded in the vertebrate eye lens. Their structures show how a simple Greek key motif can evolve rapidly to form a complex array of monomers and oligomers. Apart from remaining transparent, a major role of the partnership ofα ‐crystallins withβ ‐ andγ ‐crystallins in the lens is to form a refractive index gradient. Here, we show some of the structural and genetic features of these two protein superfamilies that enable the rapid creation of different assembly states, to match the rapidly changing optical needs among the various vertebrates.